2014
DOI: 10.1111/aepr.12050
|View full text |Cite
|
Sign up to set email alerts
|

Who Faces Higher Prices? An Empirical Analysis Based on Japanese Homescan Data

Abstract: On the basis of household-level scanner data (homescan) for Japan over a three-year period, we construct a household-level price index, and we investigate the causes of the differences in prices across households. As noted by Aguiar and Hurst (2007), large price differentials across households are observed. The differences across age and income groups, however, are small. In addition, we find that elderly people face higher prices than younger people, which is opposite of the results of Aguiar and Hurst (2007)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 12 publications
1
13
0
Order By: Relevance
“…One can observe that younger households face similar prices, but that the price level begins to rise from the 40‐ to 45‐year‐old group onward. This result is consistent with the work of Abe and Shiotani () who used similar data, but for an earlier period (2004–2006). They found that there is little difference in prices faced by those below age 45, but that prices begin to increase thereafter.…”
Section: Age and Inflation Expectationssupporting
confidence: 93%
“…One can observe that younger households face similar prices, but that the price level begins to rise from the 40‐ to 45‐year‐old group onward. This result is consistent with the work of Abe and Shiotani () who used similar data, but for an earlier period (2004–2006). They found that there is little difference in prices faced by those below age 45, but that prices begin to increase thereafter.…”
Section: Age and Inflation Expectationssupporting
confidence: 93%
“…This information, along with the date of purchase, is linked with demographic details of the household and the household purchasing history. j Outside the wine sector, Homescan data have also been used to estimate brand level price elasticities and price response elasticities (Cotterill, 1994), change in household purchasing habits due to business cycle fluctuation (Cotti et al, 2014), the influence of selected demographic variables associated with purchase of organic milk (Alviola and Capps, 2010), the effect of taxes on sales (Harding et al, 2012) and the causes of price difference across households (Abe and Shiotani, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Naohito Abe and Kyosuke Shiotani () consider the relationship between shopping behavior and price level based on commodity‐household level scanner data for Japan provided by Intage. The data contain the daily shopping information of approximately 12,000 households, randomly selected from all prefectures (except Okinawa) in Japan, and cover 3 years, from 2004 to 2006.…”
Section: Summary Of Papers and Discussionmentioning
confidence: 99%
“…Kuroda and Yamamoto () also examine the role of labor markets, especially the role of nominal wage flexibility, in the process of deflation. Abe and Shiotani () investigate the implications of deflation/inflation for income redistribution across heterogeneous households. Finally, Shioji () discusses policy options to stop deflation, with a particular focus on the exchange rate channel, which is considered to be effective even when the policy rate is already at the ZLB.…”
Section: Japan's Persistent Deflation and Monetary Policymentioning
confidence: 99%